Bottleneck-Based Heuristic for Permutation Flowshop Scheduling. Issue 1 (April 2020) - Isa, N.A.; Bareduan, S.A.; Zainudin, A.S.
Abstract: This paper addresses the permutation flowshop scheduling problem with objective of makespan minimization. It proposes a heuristic that apply bottleneck-based identification technique and Nawaz, Enscore and Ham (NEH) insertion technique. This experiment was carried out using measurement of four-machines and six-jobs simulated in Microsoft Excel Simple Programming. The computational result show that bottleneck-based (BNB) achieved 60 % and more of optimum solution and heuristic validation result prove that the proposed heuristic resulting to be much better than existing heuristic by achieving more best solution of 6 sets out of 10 sets replication.